2019
DOI: 10.48550/arxiv.1905.04852
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Is Volatility Rough ?

Abstract: Rough volatility models are continuous time stochastic volatility models where the volatility process is driven by a fractional Brownian motion with the Hurst parameter smaller than half, and have attracted much attention since a seminal paper titled "Volatility is rough" was posted on SSRN in 2014 showing that the log realized volatility time series of major stock indices have the same scaling property as such a rough fractional Brownian motion has. We however find by simulations that the impressive approach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 28 publications
2
29
0
Order By: Relevance
“…The first empirical evidences reported in [15] suggest that the logarithm of the asset price stochastic variance can be represented by a fractional Brownian motion (fBM) of Hurst exponent H close to H 0.1 < 1/2. More recent studies based either on quasi-likelihood approach [12] or GMMapproach [9], consistently suggest the H is even closer to H = 0, i.e., H 0.05 for a large panel of equity data. In that respect, it is natural to consider the limit H → 0 in the rough process driving the volatility logarithm.…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…The first empirical evidences reported in [15] suggest that the logarithm of the asset price stochastic variance can be represented by a fractional Brownian motion (fBM) of Hurst exponent H close to H 0.1 < 1/2. More recent studies based either on quasi-likelihood approach [12] or GMMapproach [9], consistently suggest the H is even closer to H = 0, i.e., H 0.05 for a large panel of equity data. In that respect, it is natural to consider the limit H → 0 in the rough process driving the volatility logarithm.…”
Section: Introductionmentioning
confidence: 80%
“…However, since historical volatility is not directly observable on financial markets, in order to consider a more realistic scenario, we decided to run the experiments directly on a price model. We consider that a "price" Xt is modelled by a Brownian motion whose variance is a log S-fBM measure dM , i.e., where MH,T is the log-fBM defined in (12) while Bt is a Brownian motion independent of MH,T . Let us notice that, when H = 0, Xt is precisely the MRW process introduced in [25,1].…”
Section: Numerical Illustrations and Empirical Performances Of The Gm...mentioning
confidence: 99%
See 1 more Smart Citation
“…From empirical studies, Gatheral et al (2018) find that the log-volatility essentially behaves like a fractional Brownian motion with Hurst exponent H of order 0.1, at any reasonable time scale. Further empirical evidence has been documented in Fukasawa et al (2019), where the authors constructed a quasi-likelihood estimator applied to realized volatility time series, and confirmed that the Hurst parameter is much smaller than half, i.e. volatility is indeed rough.…”
Section: Introductionmentioning
confidence: 82%
“…H < 1 2 . This empirical observation lead to the construction of stochastic models with strong anti-persistent volatility dynamics, the so called rough volatility models (Gatheral et al, 2018;Takaishi, 2020;Fukasawa et al, 2019;Livieri et al, 2018). One of the most leading models in this category is the rough Bergomi model (hereafter rBergomi), see (Bayer et al, 2016(Bayer et al, , 2019.…”
Section: Rough Volatilitymentioning
confidence: 99%